2008
DOI: 10.1111/j.1365-2451.2008.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

The Gash Breccias of the Pembroke Peninsula, SW Wales

Abstract: The thickest development of Carboniferous Limestone in Great Britain (about 1200 m) is in the Pembroke Peninsula of SW Wales. In various places, the regularity of the normally well-stratified limestone is broken by zones of disturbance, which are spectacularly displayed in magnificent near-vertical cliff sections. The zones generally occupy the whole of the 50 m-high cliffs and are up to 300 m wide. The chief component of these zones is a chaotic, clast-supported breccia, composed of angular limestone fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 4 publications
2
22
0
Order By: Relevance
“…3b). Walsh et al (2008) concluded that the megabreccias were formed by more than one mechanism, and suggested a third: phreatic explosion due to upward escape of thermally-driven superheated fluids (Fig. 3d).…”
Section: Previous Work and Hypothesesmentioning
confidence: 96%
See 3 more Smart Citations
“…3b). Walsh et al (2008) concluded that the megabreccias were formed by more than one mechanism, and suggested a third: phreatic explosion due to upward escape of thermally-driven superheated fluids (Fig. 3d).…”
Section: Previous Work and Hypothesesmentioning
confidence: 96%
“…Ferroan dolomite nodules occur (Walsh et al, 2008) in the breccia zones at Draught (locality 13, Fig. 2).…”
Section: Carbonate Cementmentioning
confidence: 97%
See 2 more Smart Citations
“…The aperture of resulting fault fissures at any one time is uncertain, but would have been only a fraction of the fault zone width. Although Mewslade is apparently the only example of this form of fissure fill on the Gower peninsula, examples may occur along strike to the west in Pembrokeshire (Dixon, 1921;Walsh et al 2008), and have been described from Carboniferous limestones in northwest England (Woodcock, Omma & Dickson, 2006).…”
Section: D Mewsladementioning
confidence: 99%